PARENTS' LEGAL RESPONSIBILITIES FOR THE USE OF INFORMATION MEDIA AND ELECTRONIC TRANSACTIONS BY CHILDREN IN THE CURRENT DIGITAL ERA - Tomson Situmeang; I Dewa Ayu Widyani; Andree Washington (Fakultas Hukum Universitas Kristen Indonesia, 2023)
In the digital era, especially during the current COVID-19 pandemic, the demands of parents' roles and responsibilities towards children, especially to build relationships and communicate with children, are very important and relevant. Digitization in all aspects of life after the COVID-19 pandemic has changed the way people live in general and are